Political Ideology and Organisational Espousal: A Political-Historical Analysis of Dr. John Garang De Mabior’s “New Sudan Vision” - Kuir ë Garang (Modern Africa, 2019)
The Sudan People’s Liberation Movement and Army (SPLM/A) has for decades presented a “New Sudan” as its “vision.” But SPLM/A’s official ideology was socialism and its vision a united secular and socialist Sudan. With time, this vision became “New Sudan” and its presumptive guiding ideology became “The New Sudan Vision” (NSV) without any official institutionalisation of this NSV. In fact, “NSV” does not appear in the Movement’s founding manifesto until the revision of the manifesto in 2008 when NSV was incoherently included. I argue, therefore, that the New Sudan Vision was not really an SPLM/A political ideology but John Garang’s ideology. Besides, its immediate disappearance in South Sudan after the death of John Garang and the overwhelming vote for independence was an unequivocal rejection of NSV by the South Sudanese.